PENGEMBANGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA MATA PELAJARAN PEMELIHARAAN KELISTRIKAN SEPEDA MOTOR DI SMK RISTEK JAYA JAKARTA - Purwanto, Joaozinho Joko (Jurnal Pendidikan Teknik dan Vokasional, 2022)
The purpose of this study is to develop a STAD-type cooperative learning model on the subject matter of the motorcycle filling system in the subject of motorcycle electrical maintenance in Motorcycle Business Engineering students at the Ristek Jaya Vocational High School. This research uses research and development (R&D) procedures, with the Plomp model which has the initial investigation session stage, design stage, realization stage, assessment stage and implementation stage. The STAD-type cooperative learning model was validated by two expert lecturers and one expert teacher consisting of material experts, learning model experts and lesson plan design experts, instead the feasibility trial questionnaire by 20 students. The results of material validation by material expert lecturers are in the very feasible category (85.45%), validation by learning model expert lecturers lies in the feasible category (74.28%), and the validation of lesson plan design expert teachers lies in the very feasible category (93.52%). After further validation was tried, the learning model was tested on students with a total of 20 respondents and obtained feasibility results (79.43%) which means that the model is listed in the feasible category and can be used as a learning model in the teaching and learning process.